Effect of Microfins on Thermal Performance of Microchannel Using CFD - Long Yeo, Wei; Ho Yeap, Kim; Chun Lai, Koon; Song Chee, Pei; Seng Ong, Kok (International Journal of Engineering and Technology, 2018)
In the present study, the fluid flow and heat transfer characteristic of microchannel heat sink with microfins are studied numerically at Reynold number ranging from 400 to 1200. The influence of microfins on the Nusselt number and pressure drop are investigated. Five different types of microfins namely cylindrical microfins (Case A), diverge cylindrical microfins (Case B), diverge cylindrical microfins with semi-circle rib (Case C), diverge cylindrical microfins with rectangular rib (Case D) and diverge cylindrical microfins with triangular rib (Case E) are designed. A comparative analysis of these five types of microfins with bare microchannel has been conducted. The result highlighted the extended microfins augmented the heat transfer characteristic by disrupt the thermal boundary layer. The overall thermal performances of microchannel heat sink with microfins are 1.1 â€“ 1.47 times higher compared to bare microchannel.Â Â